Peran Permodalan dalam Meningkatkan Efisiensi Biaya melalui Pengaruh Suku Bunga dan Inflasi di Sektor Perbankan - Diana Purnamasari; Muslim, Dzurotun Khanifah; Wardah Sukriya (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
Banks are financial intermediary institutions, therefore in a country a bank is needed that can carry out its functions properly and operate optimally. This study aims to determine the effect of capital, interest rates and inflation on bank cost efficiency in banks going public in 2021-2024. The data used is secondary data obtained through the idx.co.id website. The data analysis method used is multiple linear regression. The results of this study indicate that simultaneously capital, interest rates, and inflation have a significant effect on cost efficiency, partially capital and interest rates have a negative and insignificant effect on cost efficiency, partially inflation has an insignificant effect on cost efficiency. The greater the capital owned by a bank, the greater the size of the bank. Large bank capital can be channeled to third parties in the form of financing, or other investments that provide profits for the bank. if the bank's profits are large, then the bank's cost efficiency will also increase.